2019
DOI: 10.1002/admt.201900768
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Low‐Impedance Nanocomposite Comprised of Ag–Au Core–Shell Nanowires and Pt Black for Epicardial Recording and Stimulation

Abstract: Cardiac resynchronization therapy (CRT) presents effective means to modulate cardiac conduction and related functions in heart failure patients. However, the conventional CRT delivers electric current at only two points on the heart, therefore, it is unable to provide comprehensive electrical support to the heart. Additionally, the CRT‐device structure faces several issues, such as those associated with the endocardial screw tip, which may cause myocardial degeneration, and the metal lead wire, which may lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 52 publications
0
43
0
Order By: Relevance
“…Therefore, the Au‐coated Ag nanocomposite epicardial mesh could be used as a biocompatible implantable device for monitoring intracardiac electrogram and providing electrical stimulation. Sunwoo et al improved the electrical impedance to enhance the quality of the ECG signal and the feedback signal of electrical stimulation [ 121 ] ( Figure 6 a). Pt black, which is a 0D material, was added to a nanocomposite of Au‐coated Ag nanowires (140 nm mean diameter, 35 nm shell thickness, and 100 μm length) with SBS.…”
Section: Tissue‐scale Bioelectronics For In Vivo Implantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the Au‐coated Ag nanocomposite epicardial mesh could be used as a biocompatible implantable device for monitoring intracardiac electrogram and providing electrical stimulation. Sunwoo et al improved the electrical impedance to enhance the quality of the ECG signal and the feedback signal of electrical stimulation [ 121 ] ( Figure 6 a). Pt black, which is a 0D material, was added to a nanocomposite of Au‐coated Ag nanowires (140 nm mean diameter, 35 nm shell thickness, and 100 μm length) with SBS.…”
Section: Tissue‐scale Bioelectronics For In Vivo Implantationmentioning
confidence: 99%
“…Reproduced with permission. [ 121 ] Copyright 2020, Wiley‐VCH GmbH. b) Biocompatible and ultrasensitive piezoelectric effective PVDF/Dopamine OPN and pressure sensor applications.…”
Section: Tissue‐scale Bioelectronics For In Vivo Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Au shell significantly enhanced the material and biocompatibility of the device by protecting the Ag core from oxidation, which makes the nanocomposite more compatible with wearable and implantable device applications. [122] Furthermore, the phase-separated microstructure of the nanocomposite created by room temperature drying has improved the stretchability, as well as the conductivity. This performance improvement enables the electrocardiogram recording with a higher signal-to-noise ratio under the dynamic movement of the heart and provides better mechanical support for the contraction of the heart (Figure 9i).…”
Section: Stretchable Electrodes For Wearable and Implantable Devicesmentioning
confidence: 99%
“…An alternative approach makes use of all compliant material components to construct intrinsically stretchable electronic devices ( 13 , 17 , 25 ), which naturally exhibit skin-like mechanical properties without complicated structural designs. The recent studies have shown the substantial suppression of adverse reactions in these systems because of the improved mechanical compatibility with soft tissues during long-term implantable applications ( 21 , 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%